THE PERCEPTION OF MEDICAL AND PHARMACY UNDERGRADUATE STUDENTS IN YOGYAKARTA ON INTERPROFESSIONAL COLLABORATION CLASS - Saverina Nungky Dian Hapsari; Ida Ayu Triastuti (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Introduction: Improving the quality of health services requires collaborative work skills in managing health problems from health workers. An understanding about interdisciplinary collaboration needs to be given since students take theoretical education. Learning about interprofessional education (IPE) needs to be evaluated whether it provides benefits to students in achieving learning objectives. The purpose of this study was to determine student perceptions after participating in IPE collaborative learning. Method: This research is a descriptive cross-sectional quantitative study. Samples from this study were students of the UKDW Medical Faculty and the USD Pharmacy Faculty who participated in the IPE Communication Clinical Skills. A total of 269 students were given the Google Questionnaire IPE questionnaire, which was adapted from the Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE). The reliability of the questionnaire measured by Cronbach’s Alpha was 0.72. Results: The number of students who filled out the questionnaire was 176 people (response rate of 65.43%), consisting of 99 undergraduate students of the UKWD Faculty of Medicine and 170 students of the Faculty of Pharmacy. Students tend to choose to agree or strongly agree from all four research scales. Discussion: The instrument contains 10 questions and contains 3 factors that emphasize collaborative teamwork, roles and responsibilities of each profession, and patient outcomes. The total mean value of all questions shows that according to students' perceptions, interprofessional education sessions are beneficial for students in understanding these factors. The results of the study generally describe students having a positive perception about IPE learning. Conclusion: Students consider that the management of health by the interprofessional team can improve the health and satisfaction of patients, the importance of working with other professions, and understanding roles and responsibilities in collaborative practice.